2024
DOI: 10.3390/cancers16030524
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Anti-Tumor Effects of Pseudomonas aeruginosa Mannose-Sensitive-Hemagglutinin (PA-MSHA): An Overview of Positive and Negative Effects

Dragica Bozic,
Jovana Živanović,
Katarina Živančević
et al.

Abstract: Cancer is a leading cause of death worldwide, for which finding the optimal therapy remains an ongoing challenge. Drug resistance, toxic side effects, and a lack of specificity pose significant difficulties in traditional cancer treatments, leading to suboptimal clinical outcomes and high mortality rates among cancer patients. The need for alternative therapies is crucial, especially for those resistant to conventional methods like chemotherapy and radiotherapy or for patients where surgery is not possible. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Several in vitro and in vivo studies have shown that Pseudomonas aeruginosa-mannose-sensitive hemagglutinin (PA-MSHA), a genetically modified and inactivated form of Pseudomonas aeruginosa with mannose-sensitive hemagglutinin, can play an anti-tumor role by promoting cancer cell apoptosis, inhibiting cancer cell proliferation, and activating immune cells and cytotoxic effects ( 13 , 14 ). In addition to its antitumor effects, PA-MSHA has been shown in several studies to treat lymphatic leakage in radical mastectomy ( 15 ), gynecologic malignant tumor surgery ( 16 ) and radical thyroidectomy ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that Pseudomonas aeruginosa-mannose-sensitive hemagglutinin (PA-MSHA), a genetically modified and inactivated form of Pseudomonas aeruginosa with mannose-sensitive hemagglutinin, can play an anti-tumor role by promoting cancer cell apoptosis, inhibiting cancer cell proliferation, and activating immune cells and cytotoxic effects ( 13 , 14 ). In addition to its antitumor effects, PA-MSHA has been shown in several studies to treat lymphatic leakage in radical mastectomy ( 15 ), gynecologic malignant tumor surgery ( 16 ) and radical thyroidectomy ( 17 ).…”
Section: Introductionmentioning
confidence: 99%